Development of Android-Based Mobile Learning On Ecosystem Materials To Increase The Interest in Learning Elementary School Students - Linda Setiawati; Asep Sunandar; Muhammad Zidni Ilman Nafi'a; Ediyanto Ediyanto; Melor Md Yunus (Graduate School of Universitas Negeri Malang, 2023)
Abstract: The development of mobile learning ecosystem materials for elementary school students aims to produce a learning media that aims to support teachers in delivering learning materials in class while increasing interest in learning. Research and Development (R&D) is the research method used, and the Lee and Owens model is the development model used in this development. The results of this mobile learning development were validated by the validator with an average percentage of 94.5%. The results of this validation indicate that the resulting mobile learning is valid or feasible to use in the learning process in order to increase student interest in learning.